2014
DOI: 10.1186/2046-2395-3-10
|View full text |Cite
|
Sign up to set email alerts
|

Altered dietary methionine differentially impacts glutathione and methionine metabolism in long-living growth hormone-deficient Ames dwarf and wild-type mice

Abstract: BackgroundExtending mammalian health span and life span has been achieved under a variety of dietary restriction protocols. Reducing the intake of a specific amino acid has also been shown to extend health and longevity. We recently reported that methionine (MET) restriction is not effective in life span extension in growth hormone (GH) signaling mutants. To better understand the apparent necessity of GH in the ‘sensing’ of altered dietary MET, the current study was designed to evaluate MET and glutathione (GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 73 publications
(80 reference statements)
3
30
0
Order By: Relevance
“…Ames Dwarf mice mount an increased oxidative defence in the liver and show increased levels of SAM and its SAH and largely maintain cysteine and reduced glutathione levels, especially when fed low levels of methionine in the diet44 while SAM and SAH were specifically depleted in PEsen cells; Ames Dwarf mice also showed reduced levels of hypotaurine, multiple gamma glutamyl amino acids, opthalmate and noropthalmate compared to control mice44 and these metabolites were generally elevated in PEsen cells (this study and ref. 23) consistent with Ames Dwarf mouse liver cells using these antioxidant pathways to prevent senescence initiation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Ames Dwarf mice mount an increased oxidative defence in the liver and show increased levels of SAM and its SAH and largely maintain cysteine and reduced glutathione levels, especially when fed low levels of methionine in the diet44 while SAM and SAH were specifically depleted in PEsen cells; Ames Dwarf mice also showed reduced levels of hypotaurine, multiple gamma glutamyl amino acids, opthalmate and noropthalmate compared to control mice44 and these metabolites were generally elevated in PEsen cells (this study and ref. 23) consistent with Ames Dwarf mouse liver cells using these antioxidant pathways to prevent senescence initiation.…”
Section: Discussionsupporting
confidence: 58%
“…Further work will be required to established the PEsen metabolome of muscle and liver cells in vitro . There are also differences between liver and muscle in methionine metabolism4344.…”
Section: Discussionmentioning
confidence: 99%
“…Restricting a single amino acid such as methionine also increases longevity in normal rats and mice (74,83,119) yet does not impact lifespan in GH signaling mutants (Ames dwarf, GHRKO) (20). Thus intact signaling of the somatotropic pathway appears to be necessary for amino acid sensing in terms of metabolism and lifespan regulation (19). We also know that GH treatment abolishes the DR lifespan benefits in dwarf mice (30% DR started at 5 mo of age; GH administration started 2 wk after DR at 4 mg·g body wt Ϫ1 ·day Ϫ1 ) (42).…”
Section: Interventions That Alter Gh or Igf-imentioning
confidence: 99%
“…Over the last decade, evidence has mounted that certain individual amino acids (AAs), the building blocks of protein, have distinct effects on metabolism (Brown-Borg et al, 2014; Edwards et al, 2015; Grandison et al, 2009; Miller et al, 2005). In particular, several studies have observed increased serum levels of the three branched-chain amino acids (BCAAs) – leucine, isoleucine, and valine – in insulin-resistant humans, and indeed BCAA levels are predictive of development of type 2 diabetes (Lynch and Adams, 2014).…”
Section: Introductionmentioning
confidence: 99%